Creating Collective Capabilities: Women, Agency and the Politics of Representation - Tripp, Aili Mari (Columbia Journal of Gender and Law, 2010)
In her groundbreaking book, Women and Human Development,’ Martha Nussbaum builds on Amartya Sen’s human capabilities approach, which shifts the focus from “rights” to what people actually can be or do to realize their full human potential. The approach draws on a liberal philosophical framework that emphasizes individual capabilities. This Article explores the strengths and limitations of such an approach in countries that adopt non-liberal collective capability frameworks in relation to women’s rights. This Article argues that the capabilities approach needs to be understood not only as being limited to individual capabilities, but also as encompassing the collective capability to act. Moreover, the process of creating capabilities is intensely political and therefore requires agents and agency. This is not to say that the individual capabilities approach is not important, but that it is insufficient to address the issues surrounding women’s rights. The individual capabilities frame should also include collective capability frames because they are prevalent in the world today; they highlight women’s agency in creating and enhancing their own capabilities; they highlight the structural nature of gendered marginalization within institutions and the ways this impinges on individual collectivities; they emphasize the importance of political solutions to the problem of capability, since ultimately most intractable problems involving power relations can only be resolved through political struggle and accommodation; and they open up alternate ways of conceptualizing competing and conflicting rights, such as cultural versus women’s rights.